PEMBELAJARAN MATEMATIKA REALISTIK BERBASIS KONTEKSTUAL UNTUK MATERI GEOMETRI PADA SISWA KELAS VII SMPN 2 ENDE SELATAN: Pembelajaran Matematika - A. Mei; F.Y. Naja; S. Sa’o (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2020)
The Role of mathematics in the development of science and technology in everyday life is increasingly important. Therefore it is necessary to find various strategies to improve students' ability to understand mathematics so that they are able to face the problems faced. In order for mathematics learning to be meaningful then classroom learning must associate mathematical concepts with everyday student experiences. The purpose of this study is to produce learning tools and find out student learning outcomes, the type of experimental research that begins with the development of devices, in this study used descriptive analysis to determine the effectiveness of learning tools and inferential statistical analysis to find out whether student learning outcomes following realistic contextual mathematics learning better than the learning outcomes of students who take conventional learning. The results of descriptive analysis obtained realistic mathematics learning based on effective context. And the results of inferential analysis obtained learning outcomes of students who take realistic mathematics learning is better than the learning outcomes of students who take conventional learning, this can be seen by using a significant level = 5% obtained F (0.95; 2; 67) = 3.13 , means F *> F (0.95; 2; 67), then H0 is rejected. This means that the linear regression model of the experimental class and the control class are different. This shows that contextual based realistic mathematics learning can improve student learning outcomes in class VII of SMP Negeri 2 Ende Selatan